Microaggressions in the health setting - Martinho, S.; Moleiro, C.; Vauclair, C.-M. (XV PhD Meeting in Social and Organizational Psychology, 2019)
To date the study of microaggressions against healthcare professionals who belong to one or multiple social minorities has received little empirical attention. Microaggressions are everyday verbal and nonverbal indignities, promoted intentionally or by pleasant people, that often communicate distressing messages towards social minorities. Interviews with open-ended questions were conducted with healthcare professionals from social minority groups who have experienced microaggressions in their professional setting. We aim to explore and describe what sort of microaggressions occur in the health setting during their clinical practice; how these professionals deal with and manage these subtle forms of discrimination from patients and colleagues; what are their psychosocial implications (individual, bystanders, climate, and health outcomes), and how intersectional identities may increase the experience of exclusion. The sample was composed by 39 health professionals (2 psychologists, 4 nurses and 33 physicians) who self-identified as members of different stigmatized or disadvantaged groups. The interviews followed the critical incident technique as well as personal narratives, including impacts of discriminatory experiences at the distinct levels of analysis (individual, bystanders, health care climate, and patient outcomes). The association of different types of microaggressions and sociodemographic characteristics are also explored, such as: gender, age, ethnicity, sexual orientation, functional diversity, religion, or any other personal or cultural traits. A preliminary analysis of the data will be presented with examples of different types of microaggressions in the health context, i.e., microinsults, microinvalidations, and microassaults.